Gait Asymmetry in People With Parkinson’s Disease Is Linked to Reduced Integrity of Callosal Sensorimotor Regions - Fling, Brett W.; Curtze, Carolin; Horak, Fay B. (Frontiers in Neurology, 2018)
Background: Individuals with Parkinson’s disease (PD) often manifest significant temporal and spatial asymmetries of the lower extremities during gait, which significantly contribute to mobility impairments. While the neural mechanisms underlying mobility asymmetries within this population remain poorly understood, recent evidence points to altered microstructural integrity of white matter fiber tracts within the corpus callosum as potentially playing a substantial role. Objectives: The purpose of this study was to quantify spatial and temporal gait asymmetries as well as transcallosal microstructural integrity of white matter fiber tracts connecting the primary and secondary sensorimotor cortices in people with PD and age-matched control participants. Methods: Spatial and temporal gait asymmetry in the levodopa off state was assessed using an instrumented walkway. On the next day, diffusion weighted images were collected to assess white matter microstructural integrity in transcallosal fibers connecting the homologous sensorimotor cortical regions. Results: People with PD exhibited significantly more temporal and spatial gait asymmetry than healthy control subjects. Furthermore, people with PD had significantly reduced white matter microstructural integrity of transcallosal fibers connecting homologous regions of the pre-supplementary motor and supplementary motor areas (SMA), but not the primary motor (M1) or somatosensory (S1) cortices. Finally, reduced transcallosal fiber tract integrity of the pre-SMA and S1 was associated with greater step length asymmetry in people with PD. Conclusions: People with PD showed increased step length asymmetries and decreased microstructural integrity of callosal white matter tracts connecting the higher-order sensorimotor cortices (pre-SMA and SMA). The strong association between gait asymmetries and corpus collosum integrity, supports the hypothesis that reduced transcallosal structural connectivity is a significant mechanism underlying gait asymmetries in people with PD.